2020
DOI: 10.5114/pjr.2020.95441
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted magnetic resonance imaging in the evaluation of vertebral bone marrow lesions

Abstract: Purpose: To evaluate the role of diffusion-weighted magnetic resonance imaging (DW-MRI) in differentiating vertebral marrow pathologies. To determine the sensitivity, specificity, and threshold apparent diffusion coefficient (ADC) values that can aid in the differentiation of malignant from benign bone marrow lesions. Material and methods: This observational study included 100 patients, who underwent MRI examination with a 1.5 Tesla scanner. The ADC values of normal and pathological vertebrae were estimated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…The sensitivity was found to be 96.5%, specificity was 95.2%, positive predictive value was 96.5%, and negative predictive value was 95.2%. Kaur et al [24] successfully differentiated between benign and malignant diseases utilizing quantitative DW-ADC maps. They achieved high levels of sensitivity, specificity, positive predictive value, and negative predictive value by using a threshold value of 1.21 × 10 −3 mm 2 /s.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity was found to be 96.5%, specificity was 95.2%, positive predictive value was 96.5%, and negative predictive value was 95.2%. Kaur et al [24] successfully differentiated between benign and malignant diseases utilizing quantitative DW-ADC maps. They achieved high levels of sensitivity, specificity, positive predictive value, and negative predictive value by using a threshold value of 1.21 × 10 −3 mm 2 /s.…”
Section: Resultsmentioning
confidence: 99%
“…The most prevalent region of VCFs was the lumbar region (48.57%) while the cervical and sacral regions was the least injured (5.71%) for each. Kaur, et al [19] found that the lumbar region had the maximum vertebral lesions in 45.69% of the studied patients.…”
Section: Fig 4 Roc Curve Between Benign and Malignant Vertebral Fract...mentioning
confidence: 87%
“…On the other hand, the quantitative assessment of the DWI was done by measuring the ADC values as done by many authors. Kaur et al [10] proposed ROC analysis of mean ADC for 65 benign and 35 malignant lesions most of which were metastatic lesions (n=24), this yielded threshold cut off value of 1.21 x 10 -3 mm 2 /s (p value <0.05) where malignant lesions were defined to be more than 1.21 x 10 -3 mm 2 /s and benign lesions were defined to be less than 1.21 x 10 -3 mm 2 /s with sensitivity and specificity of 100% and 92.3% for differentiating benign and malignant nature of the lesions. The standard of reference was histopathological assessment, characteristic CT appearance or lesions' behavior upon 6 months follow-up.…”
Section: Discussionmentioning
confidence: 99%